DEVELOPING THE INNOVATIVE ACTIVITY OF ENGLISH LANGUAGE TEACHERS THROUGH PEDAGOGICAL REFLECTION - Khodjayeva Nilufar Salimovna (Modern American Journals, 2025)
This article is devoted to the study of pedagogical reflection as a mechanism for developing the innovative activity of English language teachers. The work analyzes the theoretical foundations of reflection, its psychological and pedagogical aspects, and its impact on teacher professional development. The practical part presents a reflection-based model of innovation and the results of experimental work conducted among English teachers. The findings reveal that systematic reflection increases teachers’ creativity, professional motivation, and readiness for innovation.
Keywords: Pedagogical reflection, innovation, English language teacher, professional development, reflective practice, digital education.